Recent trends in power electronics applications as solutions in electric railways. Issue 5 (16th March 2020) - Hayashiya, Hitoshi; Kondo, Keiichiro
Abstract : Certain applications of power electronics for railway vehicle traction systems and fixed installations are reviewed and future possibilities considering technical and social trends around railway industry are mentioned in this paper. First of all, some particularities of railway load and traction power supply system are summarized as problems to be solved by power electronics technologies. Such technologies for fixed installations and vehicle traction systems are presented and future possibilities for higher performance, minimization, and improved resilience of railway system are pointed out. © 2020 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.